2008
DOI: 10.1080/16066350801923638
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from problem gambling without formal treatment

Abstract: Understanding the process by which problem gamblers recover without formal treatment may improve both formal treatments and assist those who wish to modify their gambling behavior without seeking treatment. Study 1 assessed the recovery process in problem gamblers who had recovered for at least 6 months without formal treatment from those who had recovered with the assistance of formal treatment. The treated recovered gamblers generally had a more severe gambling problem than did untreated recovered gamblers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 23 publications
0
32
0
6
Order By: Relevance
“…There is evidence for the effectiveness of brief interventions, including Internet-based treatment and self-help options, for other addictive behaviours including gambling (Blankers, Koeter, & Schippers, 2011;Dunn, Deroo, & Rivara, 2001;Gainsbury & Blaszczynski, 2011aHodgins, Currie, & el-Guebaly, 2001;Hodgins, Currie, el-Guebaly, & Peden, 2004;Miller & Rollnick, 1991;Toneatto et al, 2008). Brief interventions are cost-effective for gamblers and intervention service providers (Emshoff, Perkins, Zimmermans, Mooss, & Zorland, 2007), are effective at increasing motivation to change, and are convenient and timely to complete.…”
Section: Brief Interventionsmentioning
confidence: 99%
“…There is evidence for the effectiveness of brief interventions, including Internet-based treatment and self-help options, for other addictive behaviours including gambling (Blankers, Koeter, & Schippers, 2011;Dunn, Deroo, & Rivara, 2001;Gainsbury & Blaszczynski, 2011aHodgins, Currie, & el-Guebaly, 2001;Hodgins, Currie, el-Guebaly, & Peden, 2004;Miller & Rollnick, 1991;Toneatto et al, 2008). Brief interventions are cost-effective for gamblers and intervention service providers (Emshoff, Perkins, Zimmermans, Mooss, & Zorland, 2007), are effective at increasing motivation to change, and are convenient and timely to complete.…”
Section: Brief Interventionsmentioning
confidence: 99%
“…Research suggests that moderate or mild problem gamblers are able to employ practical, problem-focused strategies and that such gamblers might benefit from the development of easily accessible intervention (Toneatto et al, 2008). Although the mechanisms for change remain unknown, extant research has demonstrated the benefits of self-help options (Dickerson, Hinchy, & England, 1990;Hodgins, Currie, & el-Guebaly, 2001).…”
Section: Treatments For Problem Gamblingmentioning
confidence: 99%
“…It is clear that online interventions have an important role in the treatment of addictions; which suggests that further research regarding the efficacy of online interventions specifically designed for disordered gamblers, may be beneficial. Research by Toneatto et al [32] indicates that individuals with mild to moderate gambling problems do not necessarily require formal interventions, suggesting that the development of online interventions may be particularly relevant to this population.…”
Section: Brief Cognitive Interventions For Disordered Gamblingmentioning
confidence: 99%